Titanium Is a Highly Thrombogenic Biomaterial: Possible Implications for Osteogenesis - Hong, Jaan; Andersson, Joakim; Nilsson Ekdahl, Kristina; Elgue, Graciela; Axén, Niklas; Larsson, Rolf; Nilsson, Bo (Thrombosis and Haemostasis, 1999)
Titanium has superior osteointegrating properties compared to other biomaterials. The mechanism for this is unknown. During the initial phase of bone implantation the biomaterial comes into direct contact with whole blood. In this study we use a newly developed in vitro chamber model to compare different commonly used biomaterials in contact with whole blood. These materials were selected with respect to their different osteointegrating properties in order to correlate these properties with the response to whole blood. In the presence of 3 IU/ml of heparin only titanium induced macroscopic clotting. This was reflected by the generation of thrombin-antithrombin which was much increased in blood in contact with titanium compared with steel and PVC. The coagulation activation caused by titanium was triggered by the intrinsic pathway because the generation of FXIIa-AT/C1 esterase inhibitor paralleled that of thrombin-antithrombin, and both thrombinantithrombin complex and FXIIa-AT/C1 esterase inhibitor generation were abrogated by corn trypsin inhibitor, which is a specific inhibitor of FXIIa. The binding of platelets was increased on the titanium surface compared to the other biomaterial surfaces and the state of platelet activation was much more pronounced as reflected by the levels of β-thromboglobulin and PDGF. This study indicates that titanium is unsuitable as a biomaterial in devices which are in direct contact with blood for a prolonged period. Furthermore, PDGF and other α-granule proteins e.g. TGF-β, are known to be potent promotors of osteogenesis which suggests that the pronounced thrombogenic properties of titanium might contribute to the good osteointegrating properties.